Psychological Distress in Out-Patients Assessed for Chronic Pain Compared to Those with Rheumatoid Arthritis - D. Rice; S. Mehta; A. Shapiro; J. Pope; M. Harth; P. Morley-Forster; K. Sequeira; R. Teasell (Pain Research and Management)
Background. Patients diagnosed with chronic pain (CP) and rheumatoid arthritis (RA) represent two samples with overlapping symptoms, such as experiencing significant pain. Objectives. To compare the level of psychological distress among patients diagnosed CP attending a specialist pain clinic with those attending a specialist RA clinic. Measures. A cross-sectional study was conducted at an academic specialist chronic pain and rheumatology clinic. Participants. 330 participants included a CP group (n=167) and a RA group (n=163) completed a booklet of questionnaires regarding demographic characteristics, duration, and severity of their pain. Psychological and personality variables were compared between the CP and RA participants using a Multivariate Analysis of Covariance (MANCOVA). Results. Level of psychological distress based on the subscales of the DASS (depression, anxiety, and stress), PASS (escape avoidance, cognitive anxiety, fear of pain, and physiological anxiety), and PCS (rumination, magnification, and helplessness) was significantly higher in the CP group compared to the RA group. Categorization of individuals based on DASS severity resulted in significant differences in rates of depression and anxiety symptoms between groups, with a greater number of CP participants displaying more severe depressive and anxiety symptoms. Discussion and Conclusions. This study found greater levels of psychological distress among CP individuals referred to an academic pain clinic when compared to RA patients referred to an academic rheumatology clinic.